Controlled Supramolecular Architecture Transformation from Homopolymer to Copolymer through Competitive Self‐Sorting Method. Issue 5 (23rd December 2016) - Li, Hui; Fan, Xiaodong; Min, Xin; Qian, Yongchao; Tian, Wei
Abstract : A supramolecular hyperbranched homopolymer is initially constructed by the self‐assembly of AB2 monomer. After adding CD2 monomer to the AB2 system, the initial supramolecular hyperbranched homopolymer is disrupted and then reassembles into a new supramolecular hyperbranched alternating copolymer by the competitive self‐sorting interaction. Abstract : Supramolecular copolymers can not only enrich the diversity of the polymer backbone but also exhibit certain special and improved properties compared with supramolecular homopolymers. However, the synthesis procedure of supramolecular copolymers is relatively complicated and time‐consuming. Herein, a simple transformation from an AB2 ‐based supramolecular hyperbranched homopolymer to an AB2 +CD2 ‐based supramolecular hyperbranched alternating copolymer by the "competitive self‐sorting" strategy is reported. After adding CD2 monomer, which bears a competitive neutral guest moiety (TAPN ) and two receptive benzo‐21‐crown‐7 host moieties (B21C7 ), to the as‐prepared AB2 ‐type supramolecular hyperbranched homopolymer constructed by the self‐assembly of dialkylammonium salt (DAAS, A group)‐functionalized pillar[5]arene (MeP5, B groups) monomers, the initial homopolymer structure is disrupted and then reassemble into a new supramolecular hyperbranched alternating copolymer based on the competitive self‐sorting interaction betweenMeP5 ‐TAPN andB21C7 ‐DAAS . This study supplies a convenient approach to directly transform supramolecular homopolymers into supramolecular copolymers.